The flexibility illusion: Algorithmic control and precarity in Indonesia’s gig economy - Asrori, Saifudin; Isma’il, Muhammad; Gamalinda, Eve F. (Center for Sociological Studies and Community Developmen, 2025)
This study critically examines the lived experiences of gig workers in Indonesia to interrogate the gap between the platform economy’s promise of flexibility and the structural realities of precarity. In the Global South, where weak social protections and high levels of informal employment render workers especially vulnerable, digital platforms frame gig work as a pathway to autonomy and entrepreneurship. This study argues that flexibility often functions as a rhetorical device concealing intensified algorithmic control and economic insecurity. Drawing on a qualitative case study, data were collected through 20 semi-structured interviews and non-participant observations with workers employed by a multinational beverage delivery platform in Tangerang, Indonesia. The findings reveal that gig work is shaped by algorithmic management, unstable income, psychosocial strain, and limited institutional protections, with gendered and intersectional vulnerabilities further exacerbating precarity. Far from enabling autonomy, gig labor reproduces digital Taylorism by externalizing risks while minimizing employer responsibility. These insights underscore the urgency of regulatory reforms that recognize hybrid employment status, ensure portable benefits, and implement gender-responsive protections to safeguard equity and dignity in platform-mediated work.